Analysis of the research subjects and hot topics of occupational diseases through the Web of Science from 1975 to 2021 - Saberi, Hamid Reza; Rabiei, Hadiseh; Zare, Asma; Jazari, Milad Derakhshan; Malakoutikhah, Mahdi (Frontiers in Public Health, 2022)
A variety of studies have been conducted in Occupational diseases (ODs) and this makes it difficult for researchers to identify new areas of study. Therefore, the present study was conducted by examining Web of Science data to identify hot topics and research topics on ODs. This is a scientometric study performed using CiteSpace and Gephi software for statistical analysis. The published article in Web of Sciences was searched using the keywords “Occupational disease*” OR “Occupational illness*” OR “Industrial disease*” OR “Industrial illness*”. Finally, the countries and institutions and their cooperation, the most important and main topics discussed, and the path of future progress in ODs was analyzed. Preliminary results of the study show that out of 5,947 articles. The results of important journals showed that the American Journal of Industrial Medicine with 233 articles (6.02%), Oxford Occupational Medicine, and International Archives of Occupational and Environmental Health with 86 (2.22%), and 83 (2.15%), respectively. The two producing countries are the United States and Germany, which published 628 and 419 articles, respectively. The results of hot topics showed occupational exposures, epidemiology, mental health, and respiratory diseases were the most important keywords used in these 45 years. It can be concluded that Germany, with its current development trend in the coming years, will surpass the United States based on the number of articles and gain the first rank. Also, future studies can be conducted on respiratory diseases as the most important ODs and health care work as the most important job during the past years.